Influence of lithosphere and basement properties on the stretching factor and development of extensional faults across the Otway Basin, southeast Australia. (December 2017) - Kharazizadeh, N.; Schellart, W.P.; Duarte, J.C.; Hall, M.
Abstract: The NW-SE striking Otway Basin in southeastern Australia is part of the continental rift system that formed during the separation of Australia from Antarctica. The development of this sedimentary basin occurred in two phases of Late Jurassic-Early Cretaceous and Late Cretaceous rifting. The evolution of this basin is mainly associated with extensional processes that took place in a pre-existing basement of Archean, Proterozoic to Paleozoic age. In this study, the total amounts of extension and stretching factor (β factor) have been measured for six transects across the entire passive margin of the Otway Basin region. The results show significant variation in extensional stretching along the basin, with the smallest stretching factors in the easternmost (β = 1.73, 1.9) and westernmost part of the basin (β = 2.09), and the largest stretching factors in the central part (β = 2.14 to 2.44). The domain with the lowest β factor is underlain mostly by thicker lithosphere of the Delamerian Orogen and older crustal fragments of the Selwyn Block. In contrast, the region with the largest β factor and amount of extension is related to younger and thinner lithosphere of the Lachlan Orogen. The main basement structures have been mapped throughout eastern South Australia and Victoria to examine the possible relationships between the younger pattern of extensional faults and the older basement fabrics. The pattern of normal faults varies considerably along onshore and offshore components of the Otway Basin from west to east. It appears that the orientation of pre-existing structures in the basement has some control on the geometry of the younger normal faults across the Otway Basin, but only in a limited number of places. In most areas the basement fabric has no control on the younger faulting pattern. Basement structure such as the north-south Coorong Shear Zone seems to affect the geometry of normal faults by changing their strike from E-W to NW-SE and also, in the easternmost part of the basin, the Bambra Fault changes the strike of normal faults from NW-SE to the NE-SW. Our results imply that the properties of the continental lithosphere exert a major influence on the β factor and amount of crustal extension but only a minor influence on the geometry of extensional faults. Highlights: The variation in stretching factor (β) and total amount of extensions across the whole crustal thickness in the Otway Basin is potentially controlled by lithospheric properties (age, thickness and strength). The westernmost part of the Otway Basin, with the lowest stretching factor and amount of extension, is underlain by thicker lithosphere. The stretching factor and extension gradually increases towards the central and eastern parts of the basin, which are underlain by thinner and younger lithosphere of the eastern part of the Delamerian Orogen and western part of the Lachlan Orogen. The values of the amount of extension and stretching factor derived from crustal thickness profiles are much greater than would be predicted from the extension accommodated by the extensional faults at the surface. This considerable discrepancy between equivalent transects might be due to the influence of the lower crustal rheology on the faults architecture in the upper crust and lower crustal flow. The pattern of normal faults varies considerably along onshore and offshore components of the Otway Basin. In the westernmost and easternmost parts of the basin, a number of normal faults appear to follow the strike of major pre-existing basement faults (e.g. Coorong Shear Zone in the east and Bambra Fault in the west). However, in most regions, the basement structures have no control on the formation of the younger faulting pattern, and most normal faults have formed independently.